An overview of migration in Myanmar: Findings from the Myanmar Household Welfare Survey - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
This paper provides evidence on the extent and characteristics of migration in Myanmar between December 2021 and June 2022. We use data from three rounds of the Myanmar Household Welfare Survey (MHWS), a nationally and regionally representative phone survey, to analyze migration patterns in Myanmar. The data highlights a complex situation, where there is both new migration, that is driven by conflict, and more traditional migration, that is driven by a search for better employment both within Myanmar and abroad. We find that approximately 3.6 million individuals or 6.5 percent of the population of Myanmar moved over the 6-month study period. Between December 2021 and June 2022 fleeing direct conflict was the primary driver of migration for as many as 604 thousand individuals. During the same period, approximately 2 million individuals moved in search of a job for themselves or a family member. Finally, Chin, Yangon, and Rakhine had the highest rates of migration.